2012
DOI: 10.2528/pierb12091308
|View full text |Cite
|
Sign up to set email alerts
|

Isogeometric Shape Optimization for Electromagnetic Scattering Problems

Abstract: Abstract-We consider the benchmark problem of magnetic energy density enhancement in a small spatial region by varying the shape of two symmetric conducting scatterers. We view this problem as a prototype for a wide variety of geometric design problems in electromagnetic applications. Our approach for solving this problem is based on shape optimization and isogeometric analysis. One of the major difficulties we face to make these methods work together is the need to maintain a valid parametrization of the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Furthermore, Basilevs et al [2] and Scott et al [3] have already demonstrated the efficient usage of IGA in conjunction with T-splines technology [4,5]. Shape optimization, in the context of IGA, has been presented in various works as, e.g., in [6,7,8] for the 2D case and in [9] for the 3D case. In these works, the control points are directly used as shape optimization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Basilevs et al [2] and Scott et al [3] have already demonstrated the efficient usage of IGA in conjunction with T-splines technology [4,5]. Shape optimization, in the context of IGA, has been presented in various works as, e.g., in [6,7,8] for the 2D case and in [9] for the 3D case. In these works, the control points are directly used as shape optimization parameters.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, we proceed in a standard way (see e.g. [14]). The derivative of the discrete magnetic field solution with respect to the boundary control points d ij for instance can be found by solving the auxiliary system of linear equations…”
Section: Shape Sensitivity Analysismentioning
confidence: 99%
“…In [20] a method for shape optimization using the Winslow functional is introduced. In [21] and [22] the authors use this technique to optimize the domain of interest for special applications such as vibrating membranes or conducting scatterers.…”
Section: Introductionmentioning
confidence: 99%